(untitled) (Economic studies journal, 2023)
This study aims to identify the joint audit approach as one of the recent trends in the field of the external audit profession and to test its impact on reducing audit risks of its various types (inherent risks, control risks, or discovery risks). This study relies on the questionnaire to collect its data through a selected sample from members of staff in the Accounting Department at the University of Benghazi, as well as the external auditors working in the city of Benghazi. The study concluded that there is a statistically significant effect of the joint audit approach on mitigating the risks of the audit (inherent risks, control risks, and discovery risks) in Libya. This study recommends the importance to find a mechanism for cooperation between audit offices to unify the efforts that are being made in order to develop the external audit profession and to clarify the importance of joint work between offices, the requirements for conducting it and its additional advantages.